A New Method for Extraction and Heavy Metals Removal of Abalone Visceral Polysaccharide. Issue 4 (9th August 2016) - Xu, Renjie; Chen, Meixiang; Fang, Ting; Chen, Jinquan
Abstract: This study developed a new method to extract abalone visceral polysaccharide (AVP) and remove its heavy metals (except for mercury) by combining enzymatic hydrolysis, plate frame filtration, alcohol precipitation, high activated clay absorption with cation exchange resin and anion exchange resin. Alcohol precipitation, dialysis, activated carbon adsorption and high activated clay adsorption were used to remove mercury in AVP, respectively. Results indicated that these technologies are credible that both AVP with higher purity and heavy metals in AVP met the limit of standard. High activated clay could remove mercury more efficiently and increase the yield of AVP compared with other methods. The methods of inductively coupled plasma mass spectrometry and atomic absorption spectrophotometer were established to detect cadmium, lead, arsenic, chromium, nickel and mercury of AVP, respectively. Results indicated that the established methods were credible and effective by analyzing uncertainty evaluation, recovery rates and precision. Practical Applications: AVP with higher purity and yield, content of heavy metals in AVP also met the limit of standard by the technologies of extraction and heavy metals removal of AVP. It was credible and effective for using ICP‐MS and AAS to detect cadmium, lead, arsenic, chromium, nickel and mercury of AVP, respectively. The application of these methods can help food industry to develop AVP into healthcare products and researchers in the production of abalone visceral polysaccharide.